Infertility and the Military Male - Reed-Maldonado, Amanda B.; Madden, Kristin C. (Seminars in Reproductive Medicine, 2019)
Male infertility is a condition that affects approximately 50% of infertile couples and about 30% of those couples have only male factor infertility identified. There has been speculation that male military service members may have an even greater lifetime prevalence of infertility as compared to the general population, but very few scientific publications focus on male factor infertility in the military population specifically. This review will discuss many of the unique considerations regarding male infertility in the military and highlight future opportunities for research. The military/federal health system has the potential to serve as a leader in both the delivery of health care for male factor infertility and in the clinical investigation into the etiologies of and treatments for male factor infertility.
Keywords: Male infertility; military; active duty; service members; veterans